A 2D -> 3D Polycatenated Metal-Organic Framework: Synthesis, Structure, Magnetic and Catalytic Study - Sen, Rupam
A mixed-ligand 3D metal-organic framework, [Ni(1,2-cpd)(bpe)(H2O)]n (1) [1,2-cpd = cis-cyclopentane-1,2-dicarboxylate, bpe = 1,2-di(4-pyridyl)ethylene], has been constructed. Topological analysis revealed that the structure is a 3-c uninodal 2D + 2D 3D polycatenated net with the Schlafli symbol 63. The compound is catalytically active towards the epoxidation reaction in heterogeneous media. It catalyses almost all types of olefinic substrates with equal efficiency. After reaction it can be recovered quite easily and can be used for further reaction without any loss of activity for several cycles. Variable-temperature magnetic susceptibility measurement reveals the presence of a weak antiferromagnetic interaction in compound 1.